Computational microscopy study of the granular structure and pH dependence of PEDOT:PSS. Issue 12 (11th March 2019) - Modarresi, Mohsen; Franco-Gonzalez, Juan Felipe; Zozoulenko, Igor
Abstract : A coarse grained molecular dynamics simulation for the morphology of PEDOT:PSS at different pH. Abstract : Computational microscopy based on Martini coarse grained molecular dynamics (MD) simulations of a doped conducting polymer poly(3, 4-ethylenedioxythiophene)polystyrene sulfonate (best known as PEDOT:PSS) was performed focussing on the formation of the granular structure and PEDOT crystallites, and the effect of pH on the material morphology. The PEDOT:PSS morphology is shown to be sensitive to the initial distribution of PEDOT and PSS in the solution, and the results of the modelling suggest that the experimentally observed granular structure of PEDOT:PSS can be only obtained if the PEDOT/PSS solution is in the dispersive state in the initial crystallization stages. Variation of the pH is demonstrated to strongly affect the morphology of PEDOT:PSS films, altering their structure between granular-type and homogeneous. It also affects the size of crystallites and the relative arrangement of PEDOT and PSS chains. It is shown that the crystallites in PEDOT:PSS are smaller than those in PEDOT with molecular counterions such as PEDOT:tosylate, which is consistent with the available experimental data. The predicted changes of the PEDOT:PSS morphology with variation of the pH can be tested experimentally, and the calculated atomistic picture of PEDOT:PSS films (not accessible by conventional experimental techniques) is instrumental for understanding the material structure and building realistic models of PEDOT:PSS morphology.